ATTRACTIVENESS OF THE LUZNAVA MANOR’S OFFER - Litavniece, Lienīte; Dembovska, Iveta; Silicka, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The Luznava Manor is one of the newest tourist attractions in Rezekne municipality, which is still in development. The paper is the result of the Rezekne Academy of Technologies (RTA) research grant “Feasibility study of tourism product development for the Luznava Manor”. The paper is aimed to assess the attractiveness of the Luznava Manor. The theoretical aspects of destination attractiveness and criteria for its assessment are reviewed in the paper. During the research study, the expert questionnaire was developed and practically approbated; the results of the expert survey are summarized in the paper. The attractiveness of the Luznava Manor’s offer is assessed in accordance with the following criteria: ease of access, exterior, visitors’ facilities, restrooms, staff, accessibility, nature factors, importance of culture, and services. Currently, it is relatively difficult to evaluate the Luznava Manor’s tourism product as a global or European level tourist destination. According to the authors, the Luznava Manor is rather to be considered as a tourist destination of national, regional and local significance.